An Ancient Role for a Prokineticin Domain in Invertebrate Hematopoiesis - Irene Söderhäll; Young‐A Kim; Pikul Jiravanichpaisal; So Young Lee; Kenneth Söderhäll (2005)
Abstract Hemopoietic development requires firm control of cell proliferation and differentiation. Although recent research has revealed conserved function of transcription factors and signaling pathways regulating lineage commitment in hemopoietic development in Drosophila melanogaster and vertebrates, little is known about hemopoietic cytokines among the invertebrate phyla. In the present study, we show that differentiation and growth of hemopoietic stem cells in vitro from an invertebrate, Pacifastacus leniusculus, require an endogenous cytokine-like factor, astakine, containing a prokineticin (PK) domain. Astakine induces a strong hematopoiesis response in live animals. An astakine homologue was also found in the shrimp, Penaeus monodon. So far, PK domains are only identified in vertebrates, in which they, for example, direct angiogenic growth. Our finding of the first PK-like cytokine characterized from any invertebrate provides novel information concerning the evolution of growth factors and blood cell development.